Pengaruh Motivasi dan Komunikasi Terhadap Pengembangan Sumber Daya Manusia di Bidang Industri Electronic Sports Pada Divisi Mobile Legends Bang Bang Se-Priangan Timur - Muhammad Denden Ramdani; Suci Putri Lestari; Mila Karmila (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This research was conducted with the aim to determine the effect of motivation and communication on the development of human resources in the field of the Electronoc Sports Industry (Survey on the Division of Mobile Legends Bang Bang Se-Priangan Timur). The method used in this study is a survey method using data obtained directly through questionnaires distributed to 95 respondents who are members of the Mobile Legends Division Bang Bang Se-Priangan Timur. The technique used in this research is multiple linear regression analysis. Based on the research results, it can be seen that motivation and communication simultaneously have a significant effect on the development of human resources in the electronic sports industry. Motivation partially has a significant effect on the Development of Human Resources in the Electronoc Sports Industry, and Communication partially has a significant effect on the Development of Human Resources in the Electronoc Sports Industry.